Sosialisasi Mitigasi Bencana Menggunakan Pengembangan Game Edukasi Kebakaran Di SDN Serengat Praya - Prasetyo, Ridho Budi; Rahman, Fadhillah Umar; Wiriasto, Giri Wahyu; Muljono, Agung Budi; Zairina, Zora; Fanani, Rezaldy (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Fire is one of the significant disasters, causing great losses to the environment and humans. Based on BNPB data, in 2019 there were 757 cases of fire in Indonesia, with electrical short circuits as the main cause. Fire prevention education is important, especially for young children. There are many ways to provide education to children, one of which is games. Android-based educational games can increase children's awareness of the dangers of fire and fire mitigation through a fun and interactive approach. The main objective of this socialization is to provide education to children regarding fires to increase awareness of young children about the risks and dangers of fire through an interesting and interactive game-based approach. The results of the implementation of this socialization are that it can help children understand the risks of fire and encourage safer behavior in the future.